Trophic Interactions of Mesopelagic Fishes in the South China Sea Illustrated by Stable Isotopes and Fatty Acids - Wang, Fuqiang; Wu, Ying; Chen, Zuozhi; Zhang, Guosen; Zhang, Jun; Zheng, Shan; Kattner, Gerhard (Frontiers in Marine Science, 2019)
As the most abundant fishes and the least investigated components of the open ocean ecosystem, mesopelagic fishes play an important role in biogeochemical cycles and hold potentially huge fish resources. There are major gaps in our knowledge of their biology, adaptations and trophic dynamics and even diel vertical migration (DVM). Here we present evidence of the variability of ecological behaviours (migration and predation) and trophic interactions among various species of mesopelagic fishes collected from the South China Sea indicated by isotopes (δ13C, δ15N), biomarker tools (fatty acids (FAs), and compound- specific stable isotope analysis of FAs (CSIA)). Higher lipid contents of migrant planktivorous fishes were observed with average values of 35%, while others ranged from 22 to 29.5%. These high lipids contents limit the application of 13Cbulk (bulk–tissue 13C) as diet indicator; instead 13Cextraction (the lipid extracted 13C) values were applied successfully to reflect dietary sources. The δ15N values of non-migrant planktivorous and piscivorous fishes varied in a narrow range (10.0 to 10.8‰). This small difference may be caused by the low temperature in deep ocean, which results in low metabolic rates of nitrogen. The piscivorous fishes had higher FA ratios of DHA (22:6n-3)/EPA (20:5n-3) than planktivorous fishes, which mirrored their potential carnivory. CSIA can reveal small changes in biochemical composition and distinguishes between possible dietary sources such as between the non-migrant piscivorous and the semi-migrant piscivorous fishes with significantly different δ13C values of the 20:4n-6 and 20:5n-3 FAs (p<0.01). Mesopelagic fishes exhibit complex trophic interactions revealed by molecular and CSIA tools and play a vital role in the marine “biological pump”. This knowledge is important to comprehensively evaluate the role of mesopelagic fishes in global carbon budgets.